The Health State of the Employee as the Condition of Employment Personality - A. M. Viklyuk (Сибирское юридическое обозрение, 2013)
The author analyzes the legal category of “employees' health” from the perspective of modern law and science of labor law, explores the relationship of physical and mental health condition of the person with employment personality.